Cardiovascular implanted electronic devices in people towards the end of life, during cardiopulmonary resuscitation and after death: guidance from the Resuscitation Council (UK), British Cardiovascular Society and National Council for Palliative Care. (7th June 2016) - Pitcher, David; Soar, Jasmeet; Hogg, Karen; Linker, Nicholas; Chapman, Simon; Beattie, James M; Jones, Sue; George, Robert; McComb, Janet; Glancy, James; Patterson, Gordon; Turner, Sheila; et al.
Abstract : The Resuscitation Council (UK), the British Cardiovascular Society (including the British Heart Rhythm Society and the British Society for Heart Failure) and the National Council for Palliative Care recognise the importance of providing clear and consistent guidance on management of cardiovascular implanted electronic devices (CIEDs) towards the end of life, during cardiorespiratory arrest and after death. This document has been developed to provide guidance for the full range of healthcare professionals who may encounter people with CIEDs in the situations described and for healthcare managers and commissioners. The authors recognise that some patients and people close to patients may also wish to refer to this document. It is intended as an initial step to help to ensure that people who have CIEDs, or are considering implantation of one, receive explanation of and understand the practical implications and decisions that this entails; to promote a good standard of care and service provision for people in the UK with CIEDs in the circumstances described; to offer relevant ethical and legal guidance on this topic; to offer guidance on the delivery of services in relation to deactivation of CIEDs where appropriate; to offer guidance on whether any special measures are needed when a person with a CIED receives cardiopulmonary resuscitation; and to offer guidance on the actions needed when a person with a CIED dies.